Evidências epidemiológicas sobre maus-tratos na infância e modelo experimental de estresse precoce - Viola, Thiago Wendt (2015)
Introduction : Early-life stress is thought to increase risk for developing cocaine addiction. However, the mechanisms and mediators of this relationship still not completely understood, particularly during adolescence, which is the period that drug use usually initiates.Objectives : To examine the effects of postnatal maternal separation (MS) on cocaineinduced conditioned place preference (CPP) paradigm in periadolescent mice. Additionally, to investigate if MS affects short-term spatial memory, as well as drug-free exploratory activity and anxiety-related behavior.Methods : BALB/c litters were randomly assigned to one of two groups: MS or standard rearing (SR - controls). The MS animals were subjected to a procedure that pups were separated from their dams daily for 180 minutes, from postnatal (PND) 2 to 15. The CPP was performed following three sequential phases: habituation (PND 34), conditioning (PND 35 to PND 44) and post-conditioning test (PND 45). For all phases, mice were placed into the chambers for a total of 30 minutes each day. Cocaine was administered at a dose of 20 mg/kg (i.p.). Animals also performed the open field and object recognition tasks. Behavioral data was analyzed using ANY-Maze video-tracking system.Results : MS selectively affected cocaine-induced CPP in adolescent mice, increasing the time spent in the drug-paired chamber, but exerted no influence on exploratory activity, anxiety-related behavior and short-term spatial memory.Conclusions : Separation from the primary caregiver during early life can increase reactivity to cocaine paired cues, such as a particular environment, in a developmental period with increased drug abuse vulnerability.